Can Mean Platelet Volume Be Used as a Predictor of Vascular Disease? Problems and Pitfalls - Arachchillage, Deepa R. J.; Laffan, Mike (Seminars in Thrombosis and Hemostasis, 2017)
Platelets play a pivotal role in both hemostasis and thrombosis. Increased platelet volume has several etiologies and may be secondary to a genetic variant, platelet activation, increased platelet turnover, or in response to inflammatory stimuli. There are several hereditary syndromes in which an increased mean platelet volume (MPV) occurs in association with a reduction in platelet number and function. An acquired increase in platelet size is often associated with increased platelet reactivity, shortened bleeding time, and increased platelet aggregation. Many studies have shown that high MPV is associated with increased risk of venous and arterial thrombosis, but genome-wide association analyses found a weak inverse association between the risk of coronary heart disease and MPV. The disease associations of MPV suggest that it could provide a useful contribution to risk assessment algorithms for both venous thromboembolism and arterial thrombosis. However, owing to the problems associated with reliably assessing MPV, it does not yet constitute a practically useful biomarker for this purpose. Before MPV can be adopted for wider clinical use, the methodological problems involved in obtaining accurate and interlaboratory comparable results must be resolved. In particular, a major degree of standardization is required, as are local reference ranges calculated with respect to specified time intervals from venipuncture to laboratory analysis. We discuss here the potential role of MPV in predicting the risk of acquired thrombotic disorders in addition to roles in congenital thrombocytopenic disorders, as well as the problems and pitfalls associated with use of MPV in these settings.
Keywords: platelets; mean platelet volume; thrombosis; quality control; standardization